Aktivitas Antibakteri Minyak Habbatusauda (Nigella Sativa L.) dalam Menghambat Pertumbuhan Bakteri Propionibacterium Acnes dan Staphylococcus Aureus - Darmanta Bukit; Julia Reveny; Masfria Masfria (Universitas Pahlawan Tuanku Tambusai, 2025)
ABSTRACTAcne is a common skin disorder associated with the proliferation of Propionibacterium acnes and Staphylococcus aureus. This study aims to evaluate the antibacterial activity of Nigella sativa (black seed) oil against these two bacteria and investigate its mechanism of action. The methods included disc diffusion assay for inhibition zone measurement, determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), and analysis of ion leakage and intracellular content release using spectrophotometry. The results revealed that black seed oil demonstrated antibacterial activity, with the highest inhibition zone at 100% concentration: 16.16 mm for P. acnes and 16.43 mm for S. aureus. MBC values were determined at 12.5% for P. acnes and 6.25% for S. aureus. The oil also induced leakage of Ca²⁺ and K⁺ ions, as well as nucleic acids and proteins from bacterial cells, indicating membrane disruption as its primary mechanism. These findings support the potential use of black seed oil as a natural therapeutic agent for acne treatment. Keywords: black seed oil, acne, antibacterial, Propionibacterium acnes, Staphylococcus aureus.